Effectiveness of Using E-Puskesmas Application in Public Health Centre in the Work Area at Public Health Office - Hetrianto, Novian Dwi; Pratiwi Putri, Dian Utama; Arisandi, William (PT.Mantaya Idea Batara, 2024)
The use of e-Puskesmas is an effort to provide solutions to health service providers, namely Community Health Centers so that they can provide services to patients quickly; reporting activities to the Health Service are also faster due to the Online Reporting system, making it easier for previously manual activities to become digital, and of course save time at work. The E-Puskesmas application in Kota Metro is already running in 11 Community Health Centers. This research aims to determine the effectiveness of using the e-Puskesmas application in community health center services in the work area of the Dinas Kesehatan Kota Metro in 2023. This type of research is mixed research, namely qualitative followed by quantitative (mixed method). The population in this study determined the sources/informants using a purposive sampling technique of 20 people. This research was conducted on 6-11 August 2023. Data was collected using questionnaire filling, observation, and interview techniques. The results of qualitative research based on the results of interviews conducted with key informants at 11 Community Health Centers in Kota Metro regarding efficiency indicators in the effectiveness of using the e-Puskesmas application are less effective, this can be seen from the lack of adequate human resources in each Community Health Center which is not by their competence. The results of quantitative research based on the efficiency variable were 14 respondents (87.9%) with negative answers and 6 respondents (12.1%) with positive answers. Variable adequacy: 15 respondents (85.1%) answered negatively, and 5 (14.9%) answered positively. Alignment variable: 12 respondents (87.9%) answered negatively, and 6 (12.1%) answered positively. Responsiveness variable: 12 respondents (87.9%) answered negatively and 8 (12.1%) answered positively. Variable accuracy: 15 respondents (85.1%) answered negatively, and 5 (14.9%) answered positively. Suggestions should be made to first evaluate the puskesmas by related parties, regarding the preparation and availability of the puskesmas to implement the e-puskesmas application